Does aging influence sectoral employment shares? Evidence from panel data - Ulrich Thießen; Konstantin Arkadievich Kholodilin; Boriss Siliverstovs (Deutsches Institut für Wirtschaftsforschung (DIW), 2008)
In this study, we investigate whether population aging influences employment shares in different economic sectors. To this end, we employ dynamic panel data analysis. Our unbalanced data set comprises 54 countries and extends to a maximum time period from 1970 till 2004. Our results suggest that the aging variable - approximated by the ratio of elderly either to the total population or to the labor force - does have a statistically significant differentiated impact on the employment shares when controlling for other relevant factors, e.g., income per capita, share of trade in GDP, government consumption share in GDP, population size, etc. In particular, we find that an increase in the aging proxies exerts a statistically significant adverse effect on the employment shares in agriculture, manufacturing, construction, and mining and quarrying industries. At the same time, increasing share of the elderly people in the society positively affects employment shares in community, social, and personal services as well as in the financial sector. In the simulation exercise, we illustrate the effects of aging on the employment structure within the next 45 years.
Keywords: J11; O57; C33; 330; Structural change; aging; employment shares; dynamic panel data; Sektorale Beschäftigungsstruktur; Alternde Bevölkerung; Strukturwandel; Drei-Sektoren-Hypothese; Welt